Enhanced electrodialytic bioleaching of fly ashes of municipal solid waste incineration for metal recovery. (10th June 2020) - Gomes, Helena I.; Funari, Valerio; Dinelli, Enrico; Soavi, Francesca
Abstract: Metal recovery from wastes is essential for a circular economy and minimising present-day society environmental footprint. In this study, we combined electrodialysis with bioleaching of fly ashes for enhanced metal recovery from municipal solid waste incineration residues. Results showed that the use of low-level direct current with acidophilic bacteria enhanced metal recovery in the catholyte when compared to the abiotic experiment supplied with direct current and the bioleaching experiment without direct current. The use of electrodialysis with bioleaching showed increased performance on the removal and recovery of metals in the catholyte such as Al, Cd, Co, Li, Pb, and Zn. While Co and Ni were selectively mobilised by bioleaching, Cu, Cr, Cd and Li showed highly elevated concentrations by combining both techniques. These results are proof of concept of combined methods will allow optimising the process, especially varying the liquid to solid ratio, mixing, duration of the experiments, and pH control in the anolyte. Graphical abstract: Image 1 Highlights: Proof of concept that bioleaching and electrodialysis can be combined. Electrodialysis enhanced bioleaching metal recovery from MSWI fly ashes. Substantial amounts of metals were retained in the ion exchange membrane.